2008
DOI: 10.1111/j.1540-8159.2008.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Pulmonary Vein Reconnection after Atrial Fibrillation Ablation: A Prospective Characterization of Anatomical Sites

Abstract: Acute and chronic PVR sites have a preferential distribution. This may be determined by anatomical and technical factors. Knowledge of immediate EI sites may be beneficial acutely, but with chronic PVR a careful survey is required. These findings may help target ablation, improving safety and success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
74
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 28 publications
8
74
0
4
Order By: Relevance
“…It is interesting to acknowledge that in a study evaluating acute and chronic PV reconnection after AF ablation, Rajappan et al 29 identified that besides the intervenous ridge (between ipsilateral PVs), the preferential site of acute reconnection is the PV-LAA ridge, and the preferential sites of chronic reconnections were at the PV-LAA ridge, the roof of the right superior PV, and the floor of the right inferior PV. Even though atrial arteries were not commonly found in our work at the inferior segment of the right inferior PV, atrial arteries were prevalent at the other areas described as sites of frequent reconnection.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to acknowledge that in a study evaluating acute and chronic PV reconnection after AF ablation, Rajappan et al 29 identified that besides the intervenous ridge (between ipsilateral PVs), the preferential site of acute reconnection is the PV-LAA ridge, and the preferential sites of chronic reconnections were at the PV-LAA ridge, the roof of the right superior PV, and the floor of the right inferior PV. Even though atrial arteries were not commonly found in our work at the inferior segment of the right inferior PV, atrial arteries were prevalent at the other areas described as sites of frequent reconnection.…”
Section: Discussionmentioning
confidence: 99%
“…6 Histopathology has shown variable atrial thickness around the PV ostia. In particular, important atrial muscle thickness has been observed at the ridge between the LSPV and left atrial append- Looking at the location of PV reconnections, and taking into account the impact of cryoballoon size on PV reconnection distribution, it is likely that the mechanisms leading to conduction recovery differ according to PVs: difficulty in correct positioning of the cryoballoon seems to be the predominant cause of PV reconduction at the RIPV; and geometrical mismatch between the cryoballoon and the PV ostium is likely involved in LIPV reconduction; Technological refinements of both the deflectable sheath and the cryoballoon catheter may improve energy delivery and the maintenance of PVI over time.…”
Section: Discussionmentioning
confidence: 99%
“…period of 30 to 60 minutes. 21,22 Additional RF lesions to ensure isolation of PVs showing acutely recovered conduction provides similar long-term AF control to that seen in patients without early reconnection 23 and better AF control than in cases in which early reconnection was not explored. 24 Based on these observations, some authors recommend a 60-minute waiting period after initial PVI to detect early recurrences of conduction.…”
Section: Clinical Significance Of Pv Reconnectionmentioning
confidence: 99%